2019
DOI: 10.1371/journal.ppat.1007978
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Curli CsgA Cross-β Fibril Architecture Inspire Repurposing of Anti-amyloid Compounds as Anti-biofilm Agents

Abstract: Curli amyloid fibrils secreted by Enterobacteriaceae mediate host cell adhesion and contribute to biofilm formation, thereby promoting bacterial resistance to environmental stressors. Here, we present crystal structures of amyloid-forming segments from the major curli subunit, CsgA, revealing steric zipper fibrils of tightly mated β-sheets, demonstrating a structural link between curli and human pathological amyloids. D-enantiomeric peptides, originally developed to interfere with Alzheimer’s disease-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 142 publications
1
51
0
Order By: Relevance
“…That is, a bacterial amyloid protein may influence the aggregation of neuronal proteins. Perov et al discovered structural similarity between the fibers of the best studied bacterial amyloid protein curli, and neuronal amyloids [14]. They noted that the curli protein CsgA cross-seeds the fibrillation of Aβ, as was previously proposed [10].…”
Section: Functional Bacterial Amyloid Proteins (Fuba) May Cross-seed mentioning
confidence: 79%
See 1 more Smart Citation
“…That is, a bacterial amyloid protein may influence the aggregation of neuronal proteins. Perov et al discovered structural similarity between the fibers of the best studied bacterial amyloid protein curli, and neuronal amyloids [14]. They noted that the curli protein CsgA cross-seeds the fibrillation of Aβ, as was previously proposed [10].…”
Section: Functional Bacterial Amyloid Proteins (Fuba) May Cross-seed mentioning
confidence: 79%
“…It has been observed that protein folding in an amyloid configuration is a highly conserved process throughout evolution [14]. Recently, a series of studies have shown that FUBAs may interact with neuronal proteins in the manner predicted.…”
Section: Functional Bacterial Amyloid Proteins (Fuba) May Cross-seed mentioning
confidence: 95%
“…Curli amyloid shares structural and functional features with non-bacterial amyloids. Atomic resolution imaging revealed that curli amyloid fibrils resemble the Aβ fibrils found in Alzheimer's disease 53 , and synthetic D-enantiomeric peptides designed to inhibit Aβ fibrillization also inhibit CsgA fibrillation. Curli fibrillization is also inhibited by human transthyretin, an amyloid protein responsible for cardiomyopathy and neuropathy 54 .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, under our experimental conditions, the uptake of recombinant WH1(A31V) amyloids by cells not expressing WH1(WT), but just the fluorescent proteins to which the prion-like protein was tagged, does not result in any evident toxicity for the recipient cells. Although there is no protein with a noticeable degree of sequence identity with RepA-WH1 in the human proteome (BLAST best match E-value = 0.11), it has been recently suggested that bacterial extracellular amyloids may template amyloidogenesis on human proteins implicated in neurodegeneration in spite of the lack of significant sequence similarities (Friedland and Chapman, 2017; Perov et al, 2019). This could constitute a matter of concern on the biosafety of bacterial amyloids.…”
Section: Discussionmentioning
confidence: 99%